2014
DOI: 10.1136/bcr-2013-200530
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous cholecystitis mimicking gallbladder cancer

Abstract: Xanthogranulomatous cholecystitis (XGC) is a benign, uncommon variant of chronic cholecystitis characterised by focal or diffuse destructive inflammatory process of the gallbladder (GB). Macroscopically, it appears like yellowish tumour-like masses in the wall of the GB. This article reports on a 74-year-old woman with XGC mimicking GB cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Histopathological examination is the best way to make the diagnosis with high accuracy. As in our case, it shows lipid-laden macrophages in the background of chronic inflammatory cells and fibroblasts [3,4]. Cholecystectomy is the definitive management of choice.…”
Section: Discussionsupporting
confidence: 68%
“…Histopathological examination is the best way to make the diagnosis with high accuracy. As in our case, it shows lipid-laden macrophages in the background of chronic inflammatory cells and fibroblasts [3,4]. Cholecystectomy is the definitive management of choice.…”
Section: Discussionsupporting
confidence: 68%
“…This inflammatory process of a xanthogranulomatous reaction is a rare pathological finding; however, it has been described in many organ systems including the gallbladder, kidneys, and ovaries. This reaction causes a diffusely destructive process that can be compared to chronic cholecystitis in the gallbladder but mimicking gallbladder carcinoma [8]. Xanthogranulomatous pyelonephritis, also diagnosed by histology, has also shown similar features to that of renal cell carcinoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…Few articles have been published describing the similarities and differences between XGC from gallbladder cancer[ 5 6 ] and few reports about false-positive results on FDG-PET/CT scan. [ 7 ] Several studies have shown the strong association between gallstones and XGC,[ 8 ] as seen in our case.…”
Section: Discussionmentioning
confidence: 99%